STUDY EFFECT OF A PRICE VOLATILITY ON SUPPLY RESPONSE OF CORN IN IRAQ DURING PERIOD (1980 – 2014) - & Al- Ukeili, Saleh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The aim of this study to analysis Supply Response to the Corn in Iraq for Period (1980 – 2014), And effect of Price Volatility on the Supply Response through the study of the effect the explanatory variables (Average Prices of corn, for Previou year, Area Planted For Previou Year, The weighted Price (Competitive Price), The Price of Fertilizer (Urea), Total flows of Tigris And Euphrates Rivers, The Expected Price variance) on Dependent Variable (Area Planted for Corn Crop). The results indicated A Clear Disorders (Volatility) In the Average Corn Prices for Period (1991- 1996) In other Words, The Time Series of Corn Prices, And This Was an Excuse to Go to Estimate in the ARCH Family Model. It was Selected Model EGARCH (2,2) According To The Results of Statistical Tests, Which Gave An Indication of The Preference for This Model To Others, Through The Results Equation of Supply Response Note That The coefficient of The Price To Previou Year, Which Represents The Price Elasticity of Supply In The Short Run Was Identical To The Logic of Economic Theory Signal Is Positive And The Level of Significance of 1% Amounted (0.0454), And This Proves Rational Farmers In Response To Price Increase The Area, The Cross Elasticity Came To The Logic of Economic Theory And Moral Level of Probability of 1% Amounted (-0.2414), And Results of The Price Elasticity of Supply That The offer Is Inelastic In The Short Run Because The Elasticities of The Crop Was Less Than one, As Well As The Elasticity of Supply for The Production Costs And The Elasticity of Supply For Irrigation Water Came Matching Economic Logic And Moral Level of 1%, The Price Variation Parameter Which Is A Relative Measure of Price Volatility And A Significant Came Its Signal Positive Explain The Relationship With The Planted Crop Area, As The Value of The Asymmetry Factor Positive Appeared And It’s A Significant At The Level of Probability of 1% It Confirms That The Good News (Shocks) for Farmers Have A Greater Effect on Response Changes For Random Variable Effect (Risk) of Bad News (Shocks) In The Short Run.